MANAJEMEN IMPLEMENTASI KURIKULUM 2013 - Ruslan Ruslan Ruslan (UNIVERSITAS BENGKULU, 2016)
The aim of this reseach is to describe the Management Implement Curriculum 2013. In particular, it aims to describe: 1). The planning of manajement of curriculum atthe district 05 Sindang Dataran school. 2) the implementation of manajement curriculum at the distric 05 Sindang Dataran. 3) the evaluation of manajemen curriculum at the district 05 Sindang Dataran 4) the barriers and the way how handle the manajement of curriculum.The method used inthis reseach is a discriptive qualitative. The results of the reseach shows that manajement of curriculum in 05 Sindang Dataran school worked as itwas planned.Keywords: implementation, management, curriculum